THE DOMESTIC VALUE AND GLOBAL IMPACT OF DONALD TRUMP’S AMERICA FIRST POLICY - SERYAH , Khalil; ARIBI ,Brahim (Faculty of Letters and Foreign Languages Department of English, 2018)
This work examines the nature and discusses the outcome of ‘America First’ policy that was issued by the American Republican President Donald J. Trump. The purpose of this research was to explore the new policy, and reflect on it at the domestic as well as the foreign level during the period of Trump’s first fifteen months in office. In other words, the research checks the impact of ‘America First’ policy on the domestic front and investigates its global consequences. To reach this purpose, the research relied on the observations of Trump’s speeches and declarations, international relations and economic experts’ analyses, and interviews that were conducted with them. Thus, the study revealed that Donald Trump’s new method favoured economic Nationalism, and showed that Trump’s ‘America First’ policy did not meet its optimistic expectations on the domestic front. The study has also revealed that the new policy shrank the position of the United States as an indispensable nation, alienated it from its allies and raised the tension in the Middle East demolishing any chance of peace in the region.